A comparative study on rumen ecology of water buffalo and cattle calves under similar feeding regime. Issue 4 (13th July 2020) - Wang, Qiyan; Gao, Xiaomei; Yang, Yunyan; Zou, Caixia; Yang, Yingbai; Lin, Bo
Abstract: In all, 12 male water buffalo ( Bubalus bubalis ) calves and Holstein ( Bos taurus ) calves of similar age (10 ± 5 days) were selected to explore the mechanism underlying the differences in growth performance and feed conversion ratio between the two species. The experiment contains 33 days of sucking period and 40 days of post‐weaning period. Both calves were fed the same amounts of milk in sucking period, and starter and oat grass were supplied ad libitum both before and after the weaning period. Feed intake, growth performance, ruminal fermentation parameters and the ruminal microbial community were measured the during experiment period. Results showed no differences in growth performance and feed intake between the two species in sucking period; however, the feed/gain ratio (F/G) of the water buffalo was higher than that of Holstein calve ( p  > 0.05). After weaning, the intake of starter by the Holstein calf was higher while intake of grass by the water buffalo was higher resulting in higher growth performance of and a lower F/G ratio for Holstein ( p  < 0.05). The rumen of Holstein calf showed higher levels of propionate, lower levels of acetate and branched‐chain fatty acids than that of water buffalo during both periods ( p  < 0.05). The rumen of water buffalo showed a higher number of observed bacterial species and Shannon diversity as compared with that of Holstein calf. The members belonging to the bacterial phylum Bacteroides and genus Prevotella in the rumen of Holstein calf were higher ( p  < 0.05), while Firmicutes and fibrolytic bacteria Ruminobacter and Ruminococcus were lower ( p  < 0.05) than that of water buffalo. In conclusion, the water buffalo calves demonstrated clearly of having significant population of bacterial community and better fibre digestion than those of cattle calves. Abstract : Differences in growth performance and rumen microbial community between water buffalo and Holstein calves under similar feeding conditions: a comparative study.